Self Awareness dan Perilaku Faking pada Kegiatan Wawancara Kerja Karyawan - Mukhaira El Akmal; Martha Dewi Kasih Riang Waruwu; Yuninka Cicilia Br. Sinaga; Jecika Alisya; Naween Naween (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the description of self-awareness and faking behavior in employee job interviews. This study uses a qualitative research method with a case study approach. The main subjects in this study were 5 people with the following characteristics: employees who have just worked for less than one year. The results showed that the subject showed a different picture of self-awareness and faking behavior in several aspects. Subjects are able to understand themselves, set life and career goals, build relationships with others, build diversity values, be able to balance their own needs with job demands, and develop self-control over appropriate stimuli. Meanwhile, in faking behavior during job interviews, subjects tend to prioritize physical appearance during the interview, ability to communicate and cover up negative self-images during the interview.